Money in the production function: A new Keynesian DSGE perspective. (25th June 2015) - Benchimol, Jonathan
Abstract : This article checks whether money is an omitted variable in the production process by proposing a microfounded New Keynesian Dynamic Stochastic General Equilibrium model. In this framework, real money balances enter the production function, and money demanded by households is differentiated from that demanded by firms. Using a Bayesian analysis, our model weakens the hypothesis that money is a factor of production. However, the demand of money by firms appears to have a significant impact on the economy, even if this demand has a low weight in the production process.